ORGANIZATIONAL AND EDUCATIONAL CONDITIONS FOR THE FORMATION OF EFFECTIVE MANAGEMENT IN PROFESSIONAL BOXING - Kazankapov Aman; Telakhynov Yerkin; Umirzakov Yedige (Theoretical Hypotheses and Empirical Results, 2025)
The article analyzes the organizational and pedagogical conditions for the development of management in professional boxing. Professional boxing is considered as a specific segment of the modern sports industry characterized by commercialization, high media involvement, and complex contractual relations. The structure of management in professional boxing, the role of the manager, and the content of managerial activity are examined. Special attention is paid to the functions of a professional boxing manager, including goal setting, planning, organization of bouts, motivation, control, and information support. The study substantiates key organizational and pedagogical conditions that ensure effective management development, as well as the importance of specialized education and practical training of sports managers. The findings may be applied in sports management education and professional boxing practice